AB0466 Quantiferon (QFT) identifies latent tuberculosis (LTB) but does not help the evaluation of the efficacy of prophylaxis in inflammatory arthritides. (23rd January 2014) - Peruzzi, F.; Bartalesi, F.; Attala, L.; Cavallo, A.; Fiori, G.; Maddali-Bongi, S.; Bruni, C.; Nacci, F.; Bartoli, F.; Cappelli, S.; Denaro, V.; Bartoloni, A.; et al.
Abstract : Background: The screening for LTB before anti-TNF therapy is mandatory. Tuberculin Skin Test (TST) and QFT Gold in tube (QFT-GIT) may help in the detection of LTB patients who submitted a prophylactic treatment. Objectives: Evaluate the role of by QFT-GIT in the evaluation of the efficacy of the LTB prophylaxis in patients affected by rheumatic disease Methods: Out of 561 patients (263 Rheumatoid Arthritis (AR), 126 Psoriatic Arthritis (PsA) and 73 Spondiloarthropaty (SpA), 5 Inflammatory Bowel Disease (IBD) and 94 with other immunomediated chronic disease), we performed TST and QFT as screening tests and QFT was performed at the end the prophylaxis. Results: After screening, LTB was diagnosed in 87 patients who were submitted to prophylaxis (Isoniazid for 9 months or Isoniazid plus Rifampicin for 3 months).We compared by analysis of variance the value of QFT index at the beginning and at the end the therapy (QFT-GIT medium value at the beginning 5.39 and 4.0 at the end). This comparison showed no statistically significant differences (significance value 0.31). Conclusions: QFT-GIT is helpful to identify LTB but our data show that QFT-GIT index is not useful to asses the efficacy of the TB prophylaxis and rule out during the follow up the TB re-infection. QFT may be useful in identifying the TB infection during the follow up of patients who were negative at the screening. Disclosure of Interest: None Declared